Intermaxillary forces during activator treatment. - Katsavrias, E G; Halazonetis, D J (Am J Orthod Dentofacial Orthop, 1999)
The mode of action of the activator appliance is still unclear. Apart from a possible mandibular growth enhancing effect, some investigators believe that orthopedic forces may be applied to the maxilla, contributing to Class II correction by inhibition of maxillary growth. In addition, orthodontic forces may arise that produce dentoalveolar changes. The purpose of this study was to measure the magnitude of anteroposterior intermaxillary forces during wear of the activator appliance. Ten consecutive patients with Class II dental and skeletal relationships were treated with a modified activator appliance. The appliance had maxillary and mandibular segments that could be detached from each other during the measuring session. A force transducer was placed at the anterior part of the maxillary segment, and the anteroposterior force exerted by the mandibular segment was measured. Measurements were taken in the upright and reclined position at every patient visit for a period of 6 months. Results indicated that intermaxillary forces were generally in the orthodontic range (median values of 100 gf at the upright position and 123 gf at the reclined position). A wide variation in force levels was noted, both between patients and for the same patient during the experimental period. No statistically significant change in force levels was observed during the 6 month period and no difference was noted between upright and reclined posture.
Keywords: Activator Appliances; Alveolar Process; Child; Female; Follow-Up Studies; Humans; Male; Malocclusion, Angle Class II; Mandible; Maxilla; Orthodontic Appliance Design; Posture; Stress, Mechanical; Supine Position; Tooth; Transducers